2016
DOI: 10.1038/ncomms13404
|View full text |Cite
|
Sign up to set email alerts
|

Direct identification of clinically relevant neoepitopes presented on native human melanoma tissue by mass spectrometry

Abstract: Although mutations may represent attractive targets for immunotherapy, direct identification of mutated peptide ligands isolated from human leucocyte antigens (HLA) on the surface of native tumour tissue has so far not been successful. Using advanced mass spectrometry (MS) analysis, we survey the melanoma-associated immunopeptidome to a depth of 95,500 patient-presented peptides. We thereby discover a large spectrum of attractive target antigen candidates including cancer testis antigens and phosphopeptides. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
812
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 601 publications
(889 citation statements)
references
References 68 publications
36
812
2
4
Order By: Relevance
“…This phenomenon was also observed for HLA‐B*3503 binding peptides identified by MS, which had been predicted as non‐binders 39. Furthermore, we detected peptides from the whole range of experimental binding affinities, half of them intermediate or low‐affinity binders.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This phenomenon was also observed for HLA‐B*3503 binding peptides identified by MS, which had been predicted as non‐binders 39. Furthermore, we detected peptides from the whole range of experimental binding affinities, half of them intermediate or low‐affinity binders.…”
Section: Discussionsupporting
confidence: 74%
“…Most studies to date used untargeted unbiased LC‐MS 2 detection, which detects large numbers of epitopes presented at higher abundance. Untargeted detection was used for identification of HLA binding motives,35 viral epitopes,36 and tumor mutation‐derived epitopes (neoepitopes) from cancer cell lines37, 38 or primary human tumor material 39, 40. However, this common workflow fails to identify low‐abundant peptides that might still be important for immunotherapy development.…”
Section: Discussionmentioning
confidence: 99%
“…First, the neoantigen prediction method. So far, the most useful approach for identifying T cell neoepitopes is MHC-peptide binding affinity prediction, though LC-MS/MS based method is an unbiased way to comprehensively analyze the in vivo repertoire of tumor neoantigens, its sensitivity need to be further improved [39]. Second, the optimal neoantigen-based therapeutic method in clinical trials must be established.…”
Section: Resultsmentioning
confidence: 99%
“…Yadav and colleagues 64 demonstrated that vaccination with 2 neoantigens predicted by both in silico binding-affinity algorithms and MS structural analysis resulted in therapeutic T cell responses in tumor-bearing mice. Similarly, Bassani-Sternberg and colleagues 65 compared neoantigen predictions generated by NetMHC with those predicted by MS in 5 patients with melanoma. Interestingly, none of the 11 mutant peptides identified by MS were listed among the top 10 predicted candidate peptides as determined by NetMHC, though 2 of the MS neoantigens were found to elicit patient autologous T cell responses.…”
Section: Mass Spectrometrymentioning
confidence: 99%